The implementation of accounting information systems, internal control, and work motivation on employee performance - Lusia Victolia; Amelia Setiawan; Samuel Wirawan; Hamfri Djajadikerta (International Journal of Applied Finance and Business Studies, 2023)
The success or failure of achieving company goals is based on employee performance, given their role as a planner and participants in all company activities. Hence, employee performance holds significant importance for the company’s operations. Performance in its functions is not alone but is always related to several other organizational aspects. This study aims to determine how implementing an accounting information system, internal control, and work motivation affects employee performance at the Foundation of Kalam Kudus Bandung. The independent variable in this study employed the implementation of accounting information systems, internal control, and work motivation. Meanwhile, the dependent variable in this study was employee performance. The type of data used in this study was primary data obtained from respondents' answers to questionnaires distributed and shared with 40 administrative and financial staff at the Foundation of Kalam Kudus Bandung. Data processing was carried out using SPSS software 26.0 version. The results of this study show that the implementation of accounting information systems and work motivation partially influences employee performance. In contrast, the influence of internal control on employee performance cannot be statistically proven. However, implementing accounting information systems, internal control, and work motivation entirely affect employee performance